Focal Geometry and Characteristics of Erosion-Prone Coronary Plaques in vivo Angiography and Optical Coherence Tomography Study - Cao, Muhua; Wu, Tianyu; Zhao, Jiawei; Du, Zhuo; Wang, Zhuozhong; Li, Lulu; Wei, Guo; Tian, Jinwei; Jia, Haibo; Mintz, Gary S.; Yu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study compared focal geometry and characteristics of culprit plaque erosion (PE) vs non-culprit plaques in ST-segment elevated myocardial infarction (STEMI) patients in whom optical coherence tomography (OCT) identified PE as the cause of the acute event. Background: Culprit PE is a distinct clinical entity with specific coronary risk factor profile and its own tailored management strategy. However, not all plaques develop erosion resulting in occlusive thrombus formation. Methods: Between January 2017 and July 2019, 484 STEMI patients in whom OCT at the time of primary percutaneous intervention identified PE to be the cause of the culprit lesion were enrolled in the final analysis. 484 culprit PE and 1132 non-culprit plaques were identified within 1196 imaged vessels. Results: Culprit PE were highly populated at “hot spots” within the proximal 40mm in the left anterior descending artery (LAD) and tended to cluster proximal to a nearby bifurcation mainly in the LAD. Minimal lumen area (MLA) <2.51mm2 was the optimal cut-off value of plaque luminal stenosis to discriminate culprit PE from non-culprit plaques. In the multivariable analysis, focal geometry (LAD location, distance from coronary ostium <40mm, location proximal to a nearby bifurcation), luminal narrowing (MLA <2.51mm2), and presence of cholesterol crystals were independent predictors of culprit PE irrespective of the underlying substrate [lipid-rich plaque (LRP) or non-LRP). Similarities and differences in predictors of culprit PE were found between male and female and younger and older patients. Conclusions: Irrespective of underlying lesion substrates and patient risk factors, there are lesion-specific and OCT-identifiable predictors of developing culprit PE in erosion-prone vulnerable patients.